In Appreciation of Marianne Debouzy - Dawley, Alan (Labour / Le Travail, 2000)
Discusses Debouzy's scholarly work, which is notable for its preoccupation with the social history dimensions of international capitalism. Themes include transnational approach to studies of labour migration, Americanization of French universities, American influences on the French New Left, and French and American workers.